Immunogenicity, safety and consistency of seven lots of an inactivated COVID-19 vaccine in healthy children and adolescents: a randomized, double-blind, controlled, phase IV clinical trial - Hu, Weijun; Liu, Xiaoyu; Lu, Xi; Zhang, Dan; Liu, Shuo; Gu, Xianjin; Liu, Dan; Sun, Jianwen; Zhou, Tiantian; Li, Xinge; Gao, Yongjun; Zhao, Yanwei; et al. (Frontiers in Immunology, 2024)
Background: CoronaVac has been authorized worldwide for preventing coronavirus disease 2019. Information on the safety, immunogenicity and consistency of different lots and workshops of CoronaVac is presented here.In this randomized, double-blind, phase Ⅳ clinical trial in healthy children and adolescents aged 3-17 years, we aimed to assess the lot-to-lot and workshop-to-workshop consistency, as well as immunogenicity and safety of seven lots of commercial-scale CoronaVac from three workshops. Eligible participants were enrolled into three age cohorts (3-5, 6-11 and 12-17 years). Within each cohort, participants were randomly assigned to seven groups to receive two doses of CoronaVac, with four weeks apart. Serum samples were collected before the first dose and 28 days after the second dose for neutralizing antibody testing. The primary objective was to evaluate the consistency of immune response among different lots within workshop 2 or 3, as well as among different workshops. The primary endpoint was geometric mean titer (GMT) of neutralizing antibody at 28 days after full-course vaccination.Results: Between July 27 th and November 19 th , 2021, a total of 2,520 eligible participants were enrolled. Results showed that 95% confidence intervals (CIs) of GMT ratios for all comparative groups among different lots or workshops were within the equivalence criteria of [0.67, 1.5]. The GMT and seroconversion rate for all participants were 126.42 (95%CI: 121.82, 131.19) and 99.86% (95%CI: 99.59%, 99.97%) at 28 days after two-dose vaccination. The incidences of adverse reactions were similar among seven lots, and most adverse reactions were mild in Grade 1, with no serious adverse event.: CoronaVac is well-tolerated and can elicit a good immune response among children and adolescents. Lot-to-lot consistency results indicate stable manufacturing of commercial-scale CoronaVac. Clinical trial registration: https://clinicaltrials.gov/study/NCT05112913?term=NCT05112913&rank=1, identifier NCT05112913.